Le archaiologiai della dodecapoli ionica: etnicità e scrittura della storia in Paus. VII 2, 3 ss. - Marina Polito (Erga-Logoi, 2018)
Pausanias arranges the archaiologiai of the Ionian Dodecapolis so that, for each individual city, any single piece of tradition is either accepted or rejected and put in its place in chronological order. This means writing the history. The Periegetes knows very well the so-called «panionian» version, which underlies his text; he tends to prefer this version and, when he talks about identity, he thinks according to its mechanisms. But he gives an account in which this version is mitigated through the comparison with other elaborations, and includes some aspects of these latter in his text. Pausanias integrates the «panionian» story with the local traditions of the poleis in an original account but he does this by applying the panionian perspective to the city traditions and by using and eventually adapting a chronological scheme taken from the local history or the mythography, where available, or from the oral tradition, if the collective memory preserves one.